Strengthening MSME Digital Transformation through Android-Based Geolocation Mapping: Implementation of Location-Based Services and the Haversine Formula - S. Langi, Herry; Pongoh, Johan; Sendow, Deby C.; Lewan, Yurike S.; Kantohe, Doostenreyk N. (Journal La Multiapp, 2025)
Information and Communication Technology (ICT) plays a strategic role in reducing socio-economic disparities and accelerating inclusive development, especially in rural areas. In Indonesia, Micro, Small, and Medium Enterprises (MSMEs) are the dominant sector, absorbing over 96% of the workforce and contributing around 60% to the national Gross Domestic Product (GDP). However, many MSME actors particularly in remote regions such as North Sulawesi still face challenges in accessing digital markets due to limited technology adoption and lack of business location exposure. This study aims to develop an Android-based application that integrates geolocation services through the implementation of Location-Based Services (LBS) and the Haversine formula. LBS is used to detect users' real-time locations via GPS, while the Haversine formula calculates the precise distance between users and MSME locations. The application is designed to send automatic notifications when a user is within a 1000-meter radius of a registered MSME location. This research adopts a software engineering approach through the design of context diagrams, system flowcharts, and the implementation of the Haversine algorithm using the Dart programming language. Testing results show that the distance difference between the application and Google Maps ranges only from 1.5 to 2.9 meters, and the distance calculated by the application matches 100% with online Haversine calculators. These findings indicate that the system has high accuracy and is feasible to be applied as a solution to improve MSME visibility, enhance community digital literacy, and strengthen the local economy through e-commerce.